Truth to power : public intellectuals in and out of academe - Nagy-Zekmi, Silvia, 1953-; Hollis, Karyn L., 1948- (Cambridge Scholars Pub., 2010)
The notion that public intellectuals in the U.S. are in decline has again become fashionable with their portrayal as trapped between Academe and the ""real"" world. The questions addressed by this volume are: How can the voices of scholars and erudite think.